PENGARUH SELF REGULATION TERHADAP PENYESUAIAN DIRI PESERTA DIDIK DI SMK N 3 PAYAKUMBUH - Septiani Amanda Putri; Alfi Rahmi; Fadhilla Yusri; Muhiddinur Kamal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low level of self-regulation among students. This is evident from the students' tendency to be easily provoked by emotions, leading to involvement in fights, speaking in high tones to teachers, using harsh language with peers, and an inability to regulate behavior in accordance with school norms. The inability to control emotions causes students to exhibit aggressive behavior and face difficulties adapting to social situations in the school environment. Furthermore, impulsive and disrespectful behavior toward teachers and peers indicates obstacles in adjusting to social demands and prevailing norms. Therefore, this study was conducted to determine the influence of self-regulation on the social adjustment of students at SMK N 3 Payakumbuh. This study employed a quantitative approach with a correlational method. The population of this study consisted of tenth-grade (Class X) students majoring in Hospitality at SMK N 3 Payakumbuh, with a sample size of 106 students selected using proportional random sampling. The instruments used were Self-Regulation and Social Adjustment questionnaires that had been tested for validity and reliability. Data were analyzed using simple linear regression. The results showed a positive and significant influence between self-regulation and students' social adjustment, with a significance value of 0.000 < 0.05. A coefficient value of 0.616 indicates that every increase in self-regulation is followed by an increase in social adjustment. This means that the better the students' ability to regulate and control themselves, the higher their ability to adjust within the school environment. Overall, the students' levels of self-regulation and social adjustment are in the high category.